VARIETAL FEATURES OF CARROT PLANTS (DAUCUS CAROTA L.) IN THE CONTEXT OF INDIVIDUAL VARIATION OF QUALITATIVE TRAITS - E. G. Dobrutskaya; O. V. Ushakova; A. M. Smirnova (Овощи России, 2015)
The results of evaluation of phenotypic individual variation of four cultivars (Nantskaya4, Moskovskaya zimnjaya A- 515, Marlinka, and Minor) and two hybrids (Mars F1, Gribovchanin F1) of carrot are presented. The genotype-dependence of variability of such traits as «diameter and high of leaves rosette», «leaves number», «length and width of leaf blade», «length and thickness of petiole», «length, diameter, and weight of roots» are shown. Utilization of data of phenotypic variability of studied traits for development of variety technologies of carrot is recommended. The insufficient informativeness of the coefficient of variability for estimation and selection of carrot forms for adaptivity is discussed.